Leaching and solidification behavior of Cu2+, Cr3+ and Cd2+ in the hydration products of calcium sulfoaluminate cement. (1st April 2022) - Yang, Fengming; Pang, Fangjie; Xie, Jiateng; Wang, Weijie; Wang, Wenlong; Wang, Zengmei
Abstract: Utilization of industrial solid wastes such as aluminum dust, carbide slag, red mud and flue gas desulfurization gypsum (FGD gypsum) as raw materials for the production of calcium sulfoaluminate cement (CSA) is an effective way for solid waste recycling. However, the heavy metals in these industrial solid wastes may affect the cement hydration and environment, limiting the application of CSA from solid wastes. In this work, to clarify the interaction between heavy metals and CSA, as typical heavy metals, Cu 2+, Cr 3+ and Cd 2+ were introduced with different contents. The study found that Ca 2+ in ettringite crystalline can be exchanged with Cu 2+ /Cd 2+, and Al 3+ can be exchanged with Cr 3+, and this chemical capture method can prevent the leaching of heavy metals. The ICP-OES results show that the retention ratios of Cu 2+, Cr 3+ and Cd 2+ with 2 wt% dopant were above 99.99%. Besides, the proper amount of heavy metals makes CSA hydration to maintain an alkaline environment to facilitate the crystallization and growth of ettringite. However, when content of Cr 3+ was excessive (more than 2%), the pH value declined severely, which was unfavorable to the stability of ettringite. The XPS results indicated that the Cu 2+, Cr 3+ and Cd 2+ could weaken the binding energy of Ca–O and Al–O bond, decreasing the stability of ettringite crystal, resulting to weaken the compressive strength of CSA, but all are acceptable. The hydration kinetics indicate that the Cr 3+ ions make the activation energy barrier to the hydration reaction drop drastically, resultantly, accelerating the hydration process, while Cu 2+ and Cd 2+ delayed the hydration process, maybe the origin of variation of setting time. Highlights: Cu 2+, Cr 3+ and Cd 2+ can be solidified efficiently by CSA. The ions exchange between Ca 2+ and Cu 2+ /Cd 2+, Al 3+ and Cr 3+ weakened the stability of ettringite crystal structure. Cu 2+ and Cd 2+ delayed the hydration reaction of CSA, while Cr 3+ facilitated such process.